Evaluation of the antifungal potential of Fabaceae bark extracts against wood decay fungi - do Nascimento, Cristiano Souza (2025)
The Amazon rainforest harbors diverse bioactive compounds with untapped potential for sustainable applications. This study evaluated the antifungal activity of bark extracts from eight Fabaceae species against wood decay fungi (Lenzites trabea, Pycnoporus sanguineus, and Trametes villosa). Hydroalcoholic extracts were tested in vitro to determine the antifungal index (AFI), and the chemical composition of bark and extractives was analyzed. The extracts presented fungistatic activity, with AFI values ranging from 75.05 % to 100 % at 0.10 % concentration. Mora paraensis (Pracuúba) demonstrated broad-spectrum antifungal activity at all tested concentrations (0.10 %, 1.00 %, and 2.00 %). In contrast, Pentaclethra macroloba (Paracaxi) exhibited limited efficacy, selectively inhibiting P.sanguineus and L. trabea. Chemical analysis identified tannins, flavonoids, terpenes, alkaloids, and anthraquinones as key constituents, suggesting their role in fungal inhibition. Phenolic and nitrogenous compounds correlated strongly with antifungal activity, highlighting their potential as natural fungicides. The findings support the use of Fabaceae bark extractives as sustainable alternatives to synthetic wood preservatives, promoting the sustainable utilization of forest resources. Future research should focus on optimizing extraction methods and elucidating the synergistic interactions among bioactive compounds to enhance antifungal efficacy.